دراسة التنسيق الكهرطيسي بين المحطات الميكروية والتوابع الصنعية الواقعة على المدار الثابت - يونس, معين; أحمد, عـلي (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر مشكلة التنسيق الكهرطيسي من أهم المشاكل خاصة بعد زيادة العمل على مجال ترددي راديوي واحد، مما يؤدي إلى تقاطع أطياف الإشارات جزئيا" أو كليا" وهذا يسبب وجود إشارات معيقة متبادلة على مدخل أجهزة الاستقبال. لذلك وضعت اللجنة الدولية CCIR شروط العمل والتشويش المتبادل المسموح به بين هذه الأنظمة. إن ذلك يتطلب معرفة الكثافة الطيفية للإشارات المعيقة على وحدة المساحة من مرسل المحطة الميكروية، وتحديد المسافات بين هذه المحطات، هذا يقتضي معرفة استطاعة الإشارات المعيقة التي تتعلق بزوايا ميل الاتجاه الأعظمي للإشعاع عن الاتجاه إلى المحطة المعيقة المرسلة أو المستقبلة. إن معرفة هذه الزوايا تلعب دوراً هاماً في اختبار ربح الهوائي المطلوب حسب CCIR لذلك تم حساب الزاوية بين اتجاه الإرسال الأعظمي لمحطة ميكروية والاتجاه إلى التابع الصنعي مع أخذ تأثير الانكسار عن طبقات الغلاف الجوي بالحسبان. electromagnetic compatibility is one of the most important problems, especially following the increase of work on a single range of radio frequency. This leads to the intersection of signal spectra, either partially or totally. The intersection in turn causes the presence of mutual interference signals at the entrance of reception systems. Therefore, the (CCIR)(*) put the work conditions and the allowed mutual interference among systems. This requires knowledge of spectral density of the interference signals on the area unit from the transmitter of the microwave station and specifying distances among these stations. This requires knowing the power of interference signals which is related to the angles of maximum direction slanting of the ray from transmitting or receiving interference stations. Knowing these angles plays an important role in testing the required antenna gain according to CCIR. Consequently, the angle has been calculated between the maximum transmission direction of the microwave station and the direction to satellite, taking into consideration the refraction effect of the atmospheric layers.